Development of water production function for French bean (Phaseolus vulgaris L.) for efficient water management under North Eastern Hilly region of India - MISHRA, G.P.; RAY, LALA I.P. (Journal of Soil and Water Conservation, 2025)
Due to the limitations in freshwater availability, 21st-century irrigated agriculture is more focused on enhancing water productivity over crop productivity. Considering the post-rainy season scenario under the North-Eastern hilly regions of India, the scope for assurance of irrigation is very low, which forces farmers not to go for winter crops. Winter season crops viz., Chickpea, Garden peas, and French beans hold enormous potential to address the pulses deficit with a judicious water management strategy. The water production functions (WPFs) have a greater role in judicious water usage under water scare zones. The response of crop yield to different irrigation regimes needs to be interpreted well to develop WPFs. A field trial was conducted with three replications during the 2023-24 winter season using a split-plot design with four (04) levels of available soil moisture depletion (ASMD), M1 (20% of ASMD), M2 (40% of ASMD), M3 (60% of ASMD) and M4 (80% of ASMD) under main plot and three (03) French bean varieties, Arka Arjun (V1), Arka Sharath (V2) and Zorin bean (V3) under sub-plot treatment. Under M2, irrigation regime, French bean variety Zorin bean (V3) performed better. The crop yield response to the total amount of water was established through a quadratic water production function; (y = -0.0159 x2 + 9.8331 x - 467.28; R2 = 0.96). Based on the field results it may be recommended to grow the French bean variety Zorin bean with fortnight intervals of surface irrigation.